Republic of Serbia : Financial Sector Assessment Program Update; Technical Note on Crisis Management Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Technical Note reviews crisis management framework in Serbia. In light of the banking crisis in Serbia in late 2008 and early 2009, a series of measures were introduced to urgently address stability concerns. The report recommends that crisis management memoranda of understanding (MOUs) be urgently developed with the most important home supervisors. In light of the importance of foreign banks in the Serbian market, it is also paramount that the authorities develop MOUs on crisis management with the home jurisdictions of the largest investors in the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet